História da ciência e ensino: análise do seu uso e incentivo à utilização - Oliveira, Gustavo Santana de (2018)
Analyzing the current educational context, in which teaching is often questioned, the present work proposes to better understand this context and how the application of contents that deal with subjects related to the History of Science by high school teachers occurs, besides analyzing the sources that teachers use when seeking information about the subject. In order to reach this objective, two teachers were collaborated, who spontaneously, through interview and observation of their classes, provided data to estimate a panorama about the use and knowledge of HC by the selected students. These data were later analyzed and interpreted, being complemented with the analysis and later categorization of some crucial points of the didactic material used by the teachers. As a result, we have been able to diagnose a lack of information and models of how the History of Science can be applied in high school by our collaborating teachers. From these results, an informative material was created, based on the classes taught by the teachers, so that interested teachers could be inspired and visualized a model of a text that is based on the precepts of the History of Science.